View from the Sea. Barbados Aquatic Club. - [Gibbs], [George C.] (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
A view of the Aquatic Club showing the ballroom, pier, skating rink and changing huts along the beach. This is a divided back postcard. Back of the card ; AC HT £50 F64A (Handwritten in pencil). Printed in Saxony. "This is a real photograph."
[Barbados Aquatic Club]
Landscape; Black & white; 3 ½” x 11”
Keywords: Historic buildings; Buildings; Clubs; Sports; Clubhouses; Aquatic Club